2011
DOI: 10.1093/jjco/hyr064
|View full text |Cite
|
Sign up to set email alerts
|

Primary cT2 Bladder Cancer: A Good Candidate for Radiotherapy Combined with Cisplatin for Bladder Preservation

Abstract: Cases with a primary cT2 tumor could be good candidates for BPT with radiation combined with cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The correct assessment of bladder cancer extent – both mucosal spread plus three‐dimensional tumor load – rather than relying on the conventional T‐stage system is the bottom line. For the bladder preservation technique, clinical T stage, but not the pathological T stage, are used as the disease stage . The drawbacks of the current T‐staging system has to be discussed for the preservation therapy.…”
Section: Principles Of Bladder Preservationmentioning
confidence: 99%
See 1 more Smart Citation
“…The correct assessment of bladder cancer extent – both mucosal spread plus three‐dimensional tumor load – rather than relying on the conventional T‐stage system is the bottom line. For the bladder preservation technique, clinical T stage, but not the pathological T stage, are used as the disease stage . The drawbacks of the current T‐staging system has to be discussed for the preservation therapy.…”
Section: Principles Of Bladder Preservationmentioning
confidence: 99%
“…For the bladder preservation technique, clinical T stage, but not the pathological T stage, are used as the disease stage. [5][6][7] The drawbacks of the current T-staging system has to be discussed for the preservation therapy. Koga et al propose that patients proven to be non-CR after induction CRT in bladder-sparing approaches be grouped into different risk groups for death based on conventional pathology of cystectomy specimens.…”
Section: Tumor Assessmentmentioning
confidence: 99%
“…However, a recent review of the CRT for MIBC reported that the mean 5-year overall survival (OS) after treatment was 57%, which was comparable to or better than that after radical cystectomy [3]. We also reported a bladder-preservation strategy comprising a CRT with cisplatin (CDDP-radiation [CDDP-R]) as an alternative to ORC with a 77.7% OS and a 64.5% 5-year progression-free survival (PFS) after treatment for primary clinical T2 tumors [4].…”
Section: Introductionmentioning
confidence: 99%